Research and policy in ethnic relations compromised dynamics in a neoliberal era - Husband, Charles 1944- (Contemporary issues in social policy, 2015)
This unique book explores the interaction between the academic research community and those who use its research to inform their social policy interventions, thus raising awareness of the linkages between research and social policy, particularly in the area of ethnic relations